2001
DOI: 10.1177/107484070100700105
|View full text |Cite
|
Sign up to set email alerts
|

Children in Research: Fathers in Cancer Research—Meanings and Reasons for Participation

Abstract: Fathers of chronically ill children are not well represented in the literature, and we know even less about fathers whose children are involved in clinical research. This study explores the meanings of research and reasons for participation among 12 fathers whose children were engaged in clinical cancer research. Findings revealed two general meanings of the research: the contribution of data and the effect of the intervention on the body of the child. These meanings reflected the research design of survey and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 40 publications
(26 reference statements)
0
34
0
1
Order By: Relevance
“…The final sample consisted of 16 studies (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36) . As shown in Chart 1, the articles were published between 2001 and 2013 in six different countries: Australia (N=4), the United States (N=4), Canada (N=4), Brazil (N=2), China (N=1) and Ireland (N=1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The final sample consisted of 16 studies (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36) . As shown in Chart 1, the articles were published between 2001 and 2013 in six different countries: Australia (N=4), the United States (N=4), Canada (N=4), Brazil (N=2), China (N=1) and Ireland (N=1).…”
Section: Resultsmentioning
confidence: 99%
“…United States (22) Descriptive/ Generic qualitative Semi-structured interviews N=12; age=36-59; biological fathers. Fathers of children from 8 to 20 years old, on therapeutic and non-therapeutic cancer treatments.…”
Section: Liaschenko 2001mentioning
confidence: 99%
“…[42][43][44] Consent can often be sought soon after diagnosis, at birth or when the child is very ill and the parents are distressed and vulnerable. 30,45,46 Despite such challenges, parents have reported that they, rather than doctors or nurses, should be the ones who make the decision about whether a child should enter a trial, 15,32,43,47,48 although parents value doctors' advice. 49 Making a decision for one's child is further complicated by the need to make the 'right decision' and the anticipation that one might later regret a decision.…”
Section: The Context and Experience Of Trial Recruitmentmentioning
confidence: 99%
“…43 Altruism, although frequently cited by parents as a motivation for participation in trials, 49,62,63 may be a secondary consideration in their decision. 26,45,64 The seriousness of the child's condition and the urgency surrounding trial entry and parents' resulting sense of vulnerability have also been found to be important influences on how parents experience recruitment to trials. 31,32,55,65 However, the relationship between anxiety, vulnerability and trial decisions may be mediated or moderated by factors such as trust in medical research 66 and the parent-practitioner relationship.…”
Section: Influences On Parents' Decision To Enter Their Child Into a mentioning
confidence: 99%
“…Several studies have shed light on the parental decision-making process, finding that numerous factors, including the possibility of therapeutic benefit, 1,2 altruism, [3][4][5][6] the desire to contribute to medical science, 3,6 the ratio of risks to benefits, 7 and the perception of no other alternative 2,5 weigh heavily in parental decisions to grant or to refuse consent. In a previous study, we found that parents generally have positive views of research involving newborns, with fewer than 10% of participants agreeing that undertaking research with babies was intrinsically wrong.…”
Section: Introductionmentioning
confidence: 99%